Spirituality and mental health. Issue 1 (2nd January 2020) - Kao, Larkin Elderon; Peteet, John R.; Cook, Christopher C. H.
ABSTRACT: In many contexts, emotional ailments have been considered problems of religious or spiritual origin. Historically, religious groups were often the primary providers of mental health care. This changed over time with advances in medicine and Freud's writings framing religion/spirituality (R/S) as a sign of neurosis. In the early- to mid-twentieth century, mental health and R/S were often viewed by Western clinicians and patients as separate and antithetical. Recent decades have been marked by another shift in thought, with increased interest in the overlap between mental health and R/S, and recognition that R/S may in fact serve protective and healing roles in the face of emotional suffering. There has been a concomitant increase in research investigating the connections between R/S and mental health, along with increased development and application of clinical interventions addressing the two in combination. In this narrative review, we summarize the history of how mental health and R/S have been viewed as relating to one another, recent research evidence on the effects of R/S on mental health, and clinical implications of these findings. We conclude with a discussion of ongoing challenges and opportunities in the study and application of how mental health and R/S affect one another.